2011
DOI: 10.1016/j.jpainsymman.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Accuracy When Estimating Survival Duration: The Role of the Patient's Performance Status and Time-Based Prognostic Categories

Abstract: In a patient population referred for specialist palliative care consultation with diverse diagnoses and a wide range of CES, time-based categorization of survival estimates along with PPS and possibly gender could be used to inform the CES process for individual patients. Intentionally incorporating these objective elements into what has historically been the subjective process of CES may lead to improvements in accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…Several studies have shown that clinicians are generally over optimistic in their estimates of the prognoses of terminally ill patients [9] [5] [10] [11]. It has also been shown that no subset of clinicians are better at late stage prognostication than than others [12] [13] .…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have shown that clinicians are generally over optimistic in their estimates of the prognoses of terminally ill patients [9] [5] [10] [11]. It has also been shown that no subset of clinicians are better at late stage prognostication than than others [12] [13] .…”
Section: Related Workmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Often, patients are not recognized as actively or imminently dying, 1,[8][9][10][11][12][13][14] and their suffering may be exacerbated by usual medical care, in which intensive or iatrogenically harmful treatments frequently are continued. [15][16][17][18] During this time, palliative care treatment plans can be implemented, in place of or in addition to existing care plans, to reduce suffering and improve end-of-life care.…”
Section: Introductionmentioning
confidence: 99%
“…5 Fox and coworkers found that a majority of noncancer patients meeting hospice criteria survived beyond the expected 6-month prognosis. 6 On the other hand, one recent study has found that cancer and noncancer patients referred to a palliative care service were equally likely to defy their prognosis, 13 although this latter study used specialist palliative care physicians to assess prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…We measured correlations between LOS and patient characteristics using Pearson's test. To perform multivariable regression analyses, we grouped PPS scores into low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), medium (30-40) and high (50 + ). 8 We constructed a multivariable regression model for LOS that included age and gender, as well as all factors that correlated with LOS on bivariate analysis with a p < 0.05 (the PPS and prognostic categories as well as a cancer diagnosis).…”
Section: Data Collection and Analysismentioning
confidence: 99%